A Luminogen with Aggregation‐Induced Emission Characteristics for Wash‐Free Bacterial Imaging, High‐Throughput Antibiotics Screening and Bacterial Susceptibility Evaluation. (14th July 2015) - Zhao, Engui; Chen, Yilong; Chen, Sijie; Deng, Haiqin; Gui, Chen; Leung, Chris W. T.; Hong, Yuning; Lam, Jacky W. Y.; Tang, Ben Zhong
<x xml:space="preserve">Abstract</x> A luminogen with aggregation‐induced emission characteristics is reported for bacterial imaging and antibiotics screening studies. The luminogen can light up bacteria in a wash‐free manner, which simplifies the imaging process and increases its accuracy in bacterial detection. It can also be applied to high‐throughput screening of antibiotics and fast evaluation of bacterial susceptibility, giving reliable results in less than 5 h.